2015
DOI: 10.1021/bm501613u
|View full text |Cite
|
Sign up to set email alerts
|

Type, Density, and Presentation of Grafted Adhesion Peptides on Polysaccharide-Based Hydrogels Control Preosteoblast Behavior and Differentiation

Abstract: In this work, cell-responsive polysaccharide hydrogels were prepared by a simple procedure based on the sequential bioconjugation and cross-linking of the polysaccharide backbone with bioactive peptides and poly(ethylene glycol)-bis(thiol) (PEG-(SH)2), respectively. Using thiol-ene reactions, we successfully functionalized hyaluronic acid (HA) and carboxymethylcellulose (CMC) with short and long peptides (5-mer and 15-mer derivatives, respectively) derived from adhesive proteins of bone extracellular matrix. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
4
19
0
Order By: Relevance
“…These findings reflect one of the common problems associated with non-human polysaccharide based hydrogels (carboxymethylcellulose, chitosan, alginates, etc.) utilized for tissue engineering applications, characterized by a lack of bioactivity, which usually limits cell adhesion to biomaterials and further tissue integration (Shin et al, 2004 ; Jing et al, 2015 ). One approach to promote polysaccharide biomaterials interactions with surrounding tissue has been to tether cell-binding peptides to the biomaterial, through physical or chemical modification methods, to provide biological cues to mimic cell–extracellular matrix protein interactions (Jing et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings reflect one of the common problems associated with non-human polysaccharide based hydrogels (carboxymethylcellulose, chitosan, alginates, etc.) utilized for tissue engineering applications, characterized by a lack of bioactivity, which usually limits cell adhesion to biomaterials and further tissue integration (Shin et al, 2004 ; Jing et al, 2015 ). One approach to promote polysaccharide biomaterials interactions with surrounding tissue has been to tether cell-binding peptides to the biomaterial, through physical or chemical modification methods, to provide biological cues to mimic cell–extracellular matrix protein interactions (Jing et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Maheshwari et al put forward the simple relationship between cell detachment, critical shear stress, and ligand density. However, there is a study that showed increasing the density of the adhesive peptides anchors did not lead to a plateau of initial cell spreading, but rather in a bell‐shaped cell response that varied with the nature of both polysaccharide backbone and functional peptides …”
Section: Characteristics Of Peptide Immobilized Onto the Matrix Surfacementioning
confidence: 99%
“…However, there is a study that showed increasing the density of the adhesive peptides anchors did not lead to a plateau of initial cell spreading, but rather in a bell-shaped cell response that varied with the nature of both polysaccharide backbone and functional peptides. 53 There has also been much research conducted investigating how RGD molecules are required to induce cell function. Sawyer et al 54 compared the adhesion of MSC on HA disks coated with RGD in different concentration.…”
Section: Density Of Peptide Immobilized On the Matrix Surfacementioning
confidence: 99%
“…Another study found that HA did not influence cell proliferation, but alizarin red staining confirmed that it induced osteoblast differentiation. Formation of mineralized nodules increased with the expression of osteocalcin mRNA and the number of calcium nodules formed by osteoblasts increased with the increase of the molecular weight of HA [10,12] . Other studies have confirmed the effect of HA on cell viability by an oxygen consumption assay and increased expression of type I collagen and osteonectin by immunohistochemistry [13] .…”
Section: Introductionmentioning
confidence: 96%